Manajemen Ulkus Diabetikum (Edukasi, Pelatihan dan Pendampingan) Melalui Family Care Giver Pada Penderita Diabetes Mellitus - Siti Rofiatun Rosida; Lestyani; Sudaryanto (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Diabetic ulcers are a chronic complication of DM caused by angiopathy, neuropathy and the presence of infection, also of the most detrimental and serious complications of diabetes mellitus, 10% to 25% of diabetic patients develop foot ulcers diabetes. This activity is to improve the health status of the community with diabetic who can understand the prevention and know about the basic ways of treating diabetic ulcers. In this activity, counseling/education is carried out, demonstrations of foot callus care as well as basic diabetic wound care and care giver assistance in providing diabetic foot care to diabetic. It was held on August 18 2022, at Jabung, Sragen, attended by 20 elderly Posyandu cadres and 20 family with diabetic. There was a significant increase in the level of caregiver knowledge, before being given the material the highest level was in the sufficient of 16 and in the post-test the increase was dominated by a good level of 30 people. Of the 17 diabetics, on the day 2 visit after the training, 10 were still fully dependent on providing foot care, on the day 5 visit after the training, it increased to 9 who were independent, 6 were still assisted and only 2 were fully dependent. The conclusion of this activity is an increase in ability to practice DM foot exercise as an effort to avoid the risk of blood vascular disorders, neuropathy and infection of the feet. Participants of family caregiver showed increased knowledge and ability to provide basic diabetic ulcer care.